Assessment of the Social Lost of Political Crisis in Nigeria (1960 – 2023) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Politics, since time immemorial has been the major means of administering human society. In the act of social administration, there are bound to be conflict of interests which metamorphose into crises thereby faulting the political process. This study examines the lost of political crises to the Nigerian society from independence till date. In justifying this, the study reviews the system of governance practiced, the electoral process, the political participation and other factors that constitute the Nigeria’s political culture. Structural functionalist theory, as well as the conflict theory was employed in evaluating the study. To ensure meaningful coverage of the study area, six (6) Colleges of Education (C.O.E.) was selected across the six (6) geo-political zones of Nigeria. Thirty (35) respondents were randomly selected among the staff of each of the colleges comprising of both teaching and non-teaching staff amounting to two hundred and ten (210) respondents. Eventually, one hundred and eighty (180) questionnaires were collected and used for the research. Five hypotheses were tested using the ordinal regression and non-parametric correlation (spearman’s rho) to determine the level of relationship between each pairs of the independent and dependent variables using IBM SPSS statistics 20 version software. The result revealed that bad governance was majorly responsible for political crisis which procreate institutional failure, frequency change in policies, political violence, political assassinations, economic downturn, insecurity, unemployment and low self-esteem for most citizens. In conclusion, until the Nigerian constitution re-defined politics as a social service and not social work with drastic reduction of financial attributions to political offices, the scrambling and stiff contest for political positions will continue to generate crises too disastrous for the Nigerian society. Finally, the most expensive loss of political crisis to the Nigerian society is the retardation, stagnation and retrogressiveness of social growth and development.